Encyclopedia of smart materials (John Wiley & Sons, 2002)
The book provides a preface defining what is meant by and summarizing their enormous potential: tiny sensory computers, some no larger than a dust mote, will someday fundamentally impact a multitude of industries, products, and human activities. Presently, the technologies and applications are at various stages of commercialization: piezoelectric and electrorestrictive ceramics, piezoelectric polymers, and fiber-optic sensor systems are well established, while micromachined electromechanical systems (MEMS), magnetostrictive materials, shape memory alloys (SMA) and polymers, and conductive polymers are in early stages. In two volumes, in-depth articles on various aspects of this multidisciplinary field are arranged alphabetically and include substantial bibliographies; there are no cross-references, but thematic access is afforded by the subject index in the second volume. (booknews.com)